2018
DOI: 10.1080/17461391.2018.1444094
|View full text |Cite
|
Sign up to set email alerts
|

Textured insoles reduce vertical loading rate and increase subjective plantar sensation in overground running

Abstract: The effect of textured insoles on kinetics and kinematics of overground running was assessed. 16 male injury-free-recreational runners attended a single visit (age 23 ± 5 yrs; stature 1.78 ± 0.06 m; mass 72.6 ± 9.2 kg). Overground 15-m runs were completed in flat, canvas plimsolls both with and without textured insoles at self-selected velocity on an indoor track in an order that was balanced among participants. Average vertical loading rate and peak vertical force (F) were captured by force platforms. Video f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The gradual decrease in stride length from maximalist shoes through to barefoot could be regulated by plantar-sensory feedback about braking forces. Previous work by Wilkinson et al (2018) found that increased subjective plantar sensation via textured insoles resulted in reduced stride length, increased stride frequency and reduced vertical loading rates. Though speculative, it is possible that plantar sensation of impact force decreases from barefoot to minimalist to maximalist shoe conditions with a resulting increase in stride length and reduction in stride frequency.…”
Section: Differences In Stride Length Between Barefoot Minimalist And...mentioning
confidence: 92%
“…The gradual decrease in stride length from maximalist shoes through to barefoot could be regulated by plantar-sensory feedback about braking forces. Previous work by Wilkinson et al (2018) found that increased subjective plantar sensation via textured insoles resulted in reduced stride length, increased stride frequency and reduced vertical loading rates. Though speculative, it is possible that plantar sensation of impact force decreases from barefoot to minimalist to maximalist shoe conditions with a resulting increase in stride length and reduction in stride frequency.…”
Section: Differences In Stride Length Between Barefoot Minimalist And...mentioning
confidence: 92%
“…Evidence suggests that plantar-sensory feedback is used to modify running technique to avoid painful and potentially injurious impacts [24,41,42]. Increasing plantar sensation via textured insoles has recently been shown to reduce vertical loading rate by a magnitude equal to the difference between injured and non-injured runners by reducing stride length [43]. In other work, Gruber, et al [42] investigated whether heel striking, a landing pattern associated with injury [6] and commonly seen in western populations, was related to impaired plantar-sensory feedback.…”
Section: Sensory Role Of the Footmentioning
confidence: 99%
“…Wearing CFOs is used to provide foot support and shock absorption during ground contact through re-distribution of plantar loading and a better maintenance of foot stability (Crago et al 2019 ). Prior studies investigating CFOs effects on key biomechanical indicators have reported mixed results with beneficial (Worobets et al 2014 ; Wilkinson et al 2018 ) or unchanged (Lewinson et al 2013 ) adjustments in stride pattern. Discrepant findings may relate to intrinsic properties (i.e., energy return and longitudinal bending stiffness) of tested insoles provoking specific biomechanical modifications in running gait (Sinclair et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%